2022
DOI: 10.1007/s12649-022-02000-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Transformation of Glycerol to Lactic Acid in Alkaline Medium Using Cu Catalysts Obtained from Hydrotalcite-Like Precursors

Abstract: The conversion of glycerol into lactic acid in alkaline medium using heterogeneous catalysts has been highlighted and has proved to be an e cient alternative to the conventional fermentative route. This work investigated the production of lactic acid from glycerol in alkaline medium using copper catalysts obtained from hydrotalcite-like precursors in a continuous ow reaction system and the effect of different copper loading on catalytic behaviors in terms of yield and selectivity to lactic acid. The catalysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Active components and surface acidic/basic performance play important roles in catalytic glycerol conversion to lactic acid [10,[15][16][17]. Considering that noble metal catalysts can catalyze glycerol conversion at a mild reaction temperature, whereas copper-based catalysts exhibit higher lactic acid selectivity at a higher temperature, we suggest that combining non-precious Cu with noble Au could produce good catalytic performance in glycerol conversion to lactate in an alkaline aqueous solution under anaerobic atmosphere.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Active components and surface acidic/basic performance play important roles in catalytic glycerol conversion to lactic acid [10,[15][16][17]. Considering that noble metal catalysts can catalyze glycerol conversion at a mild reaction temperature, whereas copper-based catalysts exhibit higher lactic acid selectivity at a higher temperature, we suggest that combining non-precious Cu with noble Au could produce good catalytic performance in glycerol conversion to lactate in an alkaline aqueous solution under anaerobic atmosphere.…”
Section: Introductionmentioning
confidence: 96%
“…It was reported that the glycerol conversion and lactic acid selectivity on the Cu/ZIF-8 catalyst were 97.5% and 84.2% when the glycerol conversion was conducted in sodium hydroxide aqueous solutions under an anaerobic N 2 atmosphere at 230 • C for 8 h [15]. When the synthesis of lactic acid through hydrothermal glycerol conversion in sodium hydroxide aqueous solutions was conducted on a 20CuHT catalyst bed at 240 • C, the glycerol conversion and lactic acid yield were around 96.5% and 64%, respectively [16]. It was also reported that when the hydrothermal conversion of glycerol to lactate was conducted in calcium hydroxide aqueous solutions at 230 • C, the lactate selectivity was above 91% at a glycerol conversion of around 93% [10].…”
Section: Introductionmentioning
confidence: 99%